2019
DOI: 10.1002/jia2.25353
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of service refinement and its impact on repeat HIV testing by client's access to Australia's universal healthcare system: a retrospective cohort study

Abstract: Introduction Achieving the virtual elimination of HIV requires equitable access to HIV prevention tools for all priority populations. Restricted access to healthcare means migrants face particular barriers to HIV prevention services. In February 2016, a peer‐led rapid HIV testing service for gay, bisexual and other men who have sex with men (gay and bisexual men, GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…5 Medicare has not been available to refugees who have temporary VISAs, 8 meaning they have not been able to pay for counselling, medication and other health support, increasing stress and the risk of health problems. 5,[9][10][11][12][13] Many migrants face similar challenges as refugees with COVID-19. Finding culturally and linguistically appropriate information and support for dealing with stress, depression and other mental health conditions during the pandemic has been very challenging.…”
Section: Refugees and Migrants Covid-19 And Health And Technology Policy In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…5 Medicare has not been available to refugees who have temporary VISAs, 8 meaning they have not been able to pay for counselling, medication and other health support, increasing stress and the risk of health problems. 5,[9][10][11][12][13] Many migrants face similar challenges as refugees with COVID-19. Finding culturally and linguistically appropriate information and support for dealing with stress, depression and other mental health conditions during the pandemic has been very challenging.…”
Section: Refugees and Migrants Covid-19 And Health And Technology Policy In Australiamentioning
confidence: 99%
“…Additional Medicare items may also help. By adding specific videoconferencing and telephone services Medicare items for refugees and migrants, it can improve access to support for their specific needs, such as trauma and related mental health conditions, dental health, 11 sexual and reproductive health and immunisation, 10 , 23 and help reduce the likelihood of some refugee health conditions becoming chronic. 13 With access to government subsidised telehealth and specific Medicare items, many refugee and migrants on temporary VISAs are likely to have another option for meeting their physical and psychological needs.…”
Section: Who Guidelines and Opportunities For More Inclusive Teleheal...mentioning
confidence: 99%
“…Barriers to HIV testing include low perceived risk of infection, the stress of waiting for results, and fear of a positive result 8 . Men born overseas who have sex with men face additional barriers, particularly those without health insurance, including the cost of HIV testing, 9 poor awareness of HIV testing locations, cultural stigmatisation associated with HIV diagnoses, and fear of judgement by health care providers 10 . HIV self‐testing can circumvent some of these barriers, allowing men to undergo private testing, to obtain results rapidly, and to eliminate the need to attend a healthcare facility for testing.…”
mentioning
confidence: 99%
“…Two studies indicated that rapid HIV testing was performed by the intervention team (including peers). 33 , 41 However, in other studies, peers only suggested the immigrants take HIV tests and referred them to the center.…”
Section: Resultsmentioning
confidence: 99%